PROGRESSION FROM ACUTE KIDNEY INJURY TO CHRONIC KIDNEY DISEASE: A PEDIATRIC PERSPECTIVE: An invited review for Advances in Chronic Kidney Disease - Goldstein, Stuart L. (2008)
While emerging evidence indicates that the incidence of both acute kidney injury (AKI) and chronic kidney disease (CKD) in children is rising, and the etiologies are dramatically changing, relatively little is currently known regarding the potential for transition from AKI to CKD. In both situations, early intervention can significantly improve the dismal prognosis. However, the lack of a uniform AKI definition and the paucity of early, predictive biomarkers have impaired our ability diagnose AKI early to institute potentially effective therapies in a timely manner. Fortunately, recent data has validated a multi-dimensional AKI classification system for children. In addition, the application of innovative technologies has identified candidates that are emerging as early biomarkers of both AKI and CKD. These include neutrophil gelatinase-associated lipocalin (NGAL), liver-type fatty acid binding protein (L-FABP) and kidney injury molecule-1 (KIM-1). Studies to validate the sensitivity and specificity of these biomarkers in clinical samples from large cohorts and from multiple clinical situations are currently in progress, facilitated by the development of commercial tools for the reproducible measurement of these biomarkers across different laboratories.